Incidencia de la vegetación en la remoción de materia orgánica en aguas residuales urbanas - Chávez Quilumba, Morelia Alexandra (2019)
The present study evaluated the incidence of different types of vegetation in the removal of organic matter from the effluent of the oxidation lagoon of Calceta city in Bolívar canton; for this, a completely randomized bifactorial experimental design was used, which were: type of vegetation and number of cuttings, with six treatments and replicated three times. A volume of 20 liters of wastewater was used for each experimental unit obtained from the aforementioned effluent BOD5, turbidity, pH and temperature were monitored every seven days. The initial values were 450 mg/dm3 of BOD5, 83.05 NTU turbidity, 7.8 pH, 21.4°C, these values were compared with the results obtained in week three to determine the efficiency of the treatments. It was evidenced that the T4 treatment in which vetiver grass (Chrysopogon zizanioides) was used with 9 cuttings showed greater removal efficiency in BOD5 which was 108.0 (89.85%) and 24.53 (88.59%) in turbidity with averages of 7.1 pH and 22.7°C, while the T1 in which papyrus (Cyperus papyrus) was applied with 9 cuttings showed lower removal efficiency in BOD5 of 188.6 (79.11%) and 41, 77 (64.57%) in turbidity with averages of 7.3 pH and 22.8°C. Finally, with the analysis of variance, the hypothesis is accepted indicating that with the use of vegetation cover such as vetiver grass (Chrysopogon zizanioides) organic matter removals greater than 52% are achieved in the urban wastewater of Calceta.